Inosine pranobex is safe and effective for the treatment of subjects with confirmed acute respiratory viral infections: analysis and subgroup analysis from a Phase 4, randomised, placebo-controlled, double-blind study - Jiří Beran; Eva Šalapová; Marian Špajdel; on behalf of the Isoprinosine Study (EWO ISO-2014/1) Team (BMC Infectious Diseases, 2016)
Abstract Background Inosine pranobex (Isoprinosine®) is an immunomodulatory drug approved in several countries for the treatment of viral infections. This study compared the efficacy and safety of inosine pranobex versus placebo in subjects with clinically diagnosed influenza-like illness, including subjects with laboratory-confirmed acute respiratory viral infections. Subgroup analyses evaluated the efficacy of inosine pranobex compared to placebo in otherwise healthy (without related ongoing disease) subjects that were less than 50 years of age and healthy subjects that were at least 50 years of age. The effect of body mass index (BMI) was evaluated in subjects less than 50 years of age. Methods A total of 463 subjects were randomly assigned to receive inosine pranobex (n = 231) or placebo (n = 232) in this Phase 4, randomised, double-blind, multicentre study. The primary efficacy endpoint was time to resolution of all influenza-like symptoms present at baseline to none. Safety was evaluated through analysis of adverse events, vital signs, and physical examinations. Results The difference in time to resolution of all influenza-like symptoms between treatment groups was not statistically significant but showed a faster improvement in subjects in the inosine pranobex group versus those in the placebo group - Hazard Ratio = 1.175; (95 % CI: 0.806–1.714). P-value = 0.324. In the subgroup analysis for subjects less than 50 years of age, statistically significant differences in time to resolution of influenza-like symptoms that favoured the inosine pranobex group over the placebo group were observed in those without related ongoing disease and those who were non-obese (BMI <30 kg/m2). The differences between the inosine pranobex and placebo groups in subjects at least 50 years of age without related ongoing disease and in subjects less than 50 years of age who were obese (BMI ≥30 kg/m2) were not statistically significant. Inosine pranobex was generally well tolerated, and no deaths were reported. Conclusions The study results indicate the safety of inosine pranobex for the treatment of subjects with confirmed acute respiratory viral infections and confirm the efficacy of inosine pranobex versus placebo in healthy non-obese subjects less than 50 years of age with clinically diagnosed influenza-like illnesses. Trial registration EWO-ISO-2014/1, EudraCT 2014-001863-11 ; Date of registration: 29 APR 2014; Detail information web link: https://www.clinicaltrialsregister.eu/ctr-search/trial/2014-001863-11/results